2018
DOI: 10.1002/jbm4.10055
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Burden of Fractures in People Living With HIV

Abstract: The survival of people living with human immunodeficiency virus (HIV) has increased markedly since the advent of antiretroviral therapy (ART). However, other morbidities have emerged, including osteoporosis. The estimated incidence of fractures at any site in people living with HIV ranges from 0.1 per 1000 person‐years to 8.4 per 1000 person‐years: at least twice that of people without HIV. This increased risk seems to be related to HIV itself and its treatment. Risk factors for bone disease in HIV‐positive (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…6 ). Another patient was living with human immunodeficiency virus (HIV) which has been associated with a higher fracture risk [ 50 , 51 ], and one patient was treated for osteoporosis. Osteoporosis has been considered a risk factor for acromion and scapular spine fractures after RSA in previous studies [ 21 , 24 , 27 , 29 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Another patient was living with human immunodeficiency virus (HIV) which has been associated with a higher fracture risk [ 50 , 51 ], and one patient was treated for osteoporosis. Osteoporosis has been considered a risk factor for acromion and scapular spine fractures after RSA in previous studies [ 21 , 24 , 27 , 29 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection or several components of antiretroviral cocktail therapy could cause to bone loss. 20,21 Therefore, it is difficult to confirm the correlation between TDF and mandibular osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another meta-analysis including 10 studies showed that HIV-positive patients had a 2.17-fold greater risk for all fractures than HIV-negative individuals [1]. It is important to note that 19 out of the 20 studies included in these two meta-analyses were carried out in men aged 36 to 55 years [1,7].…”
Section: Introductionmentioning
confidence: 98%
“…in a meta‐analysis found a crude incidence ratio of 1.58 (95% confidence interval (CI) 1.25 to 2.00) for any fracture in HIV‐positive patients compared with HIV‐negative individuals . Similarly, another meta‐analysis including 10 studies showed that HIV‐positive patients had a 2.17‐fold greater risk for all fractures than HIV‐negative individuals . It is important to note that 19 out of the 20 studies included in these two meta‐analyses were carried out in men aged 36 to 55 years .…”
Section: Introductionmentioning
confidence: 98%